Rancang Bangun Automatic Water Filling Tub System Menggunakan Algoritma Fuzzy Mamdani - Siti Nafiah; Mochammad Hannats Hanafi Ichsan; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The water is very important things in human life. That role we can see from the level of human needs, especially when the human using the water in everyday life. But it is unfortunately if that water are waste every day because the human are negligence for himself. Today when the human charge their bathub home there are still use the principle of charging manually, it means still require the human power to operate it. Because those human still use the principle of charging manually it will be less efficient, less saving time, and less saving. In this research we made an Automatic Water Filling system which using the Fuzzy Mamdani logic method. The inputs in this system consists of 3, there are, the water level input from the HC-SR04 ultrasonic sensor, the amount of water which released will calculated using the waterflow sensor G1 / 2, and then calculates the tube size volume obtained from user input using the 4x3 keypad. And then, it will be processes by Arduino Uno Microcontroller and the output system will be displayed on the LCD. The implementation of Fuzzy Mamdani logic in automatic filling bathub consists of four stages there are, Formation of fuzzy set, Application function implication, Composition rule, and Defuzzification. The output on this system is the duration time when filling the bathtub. The success rate of Fuzzy logic we can see by comparing the output value from the system with MATLAB. The average accuracy output system is 94.90%.